Comparative Viability of Acacia auriculiformis, Eucalyptus globulus, Casuarina equisetifolia and Ailanthus malabarica under Social Forestry Plantations in Kerala - an Analysis - Stephanson, K. A. (Indian Forester, 2007)
Social Forestry has come to be recognized as one of the most important activities in forestry in a country like India where the population is large and resources are limited. The Father of our Nation eloquently conceptualized social forestry in terms of its benefits - "an ideal village should be so conditioned that the villagers could procure all their needs and requirements of the material of thatch, bamboo, fuelwood, grazing etc. from within a radius of 5 miles". The traditional production forestry can no longer meet the growing demand for wood products. The uniqueness of social forestry is that it aims at creating small forests close to human habitation for providing small timber and firewood along with carrying out afforestation works in the deforested areas. This is called social forestry because unlike traditional production or protection forestry, the responsibilities of raising, protecting and maintaining forests lie with the people, technical and institutional support from the Forest Department. It is a programme of land transformation designed to improve ecological, environmental and economic conditions of the society.